NEUROPROTECTANT OF 7,8-DIHYDROXYFLAVONE IN ISCHEMIC STROKE THROUGH MODULATION GLUTATHIONE S-TRANSFERASE AND TYROSINE RECEPTOR KINASE C: A BIOINFORMATICS STUDY - Aldita Husna Violita; Safira Dita Arviana; Rislan Faiz Muhammad; Basyar Adnani; Titin Andri Wihastuti; Husnul Khotimah; Shahdevi Nandar Kurniawan; Yuyun Yueniwati (MNJ (Malang Neurology Journal), 2023)
Background: Times New Roman 9, single space, contains the brief description of the research. Stroke is the greatest cause of disability and mortality worldwide. Several biological mechanisms underlying this disease such as failure of glutamate reuptake and ATP synthesis, resulting in high levels of reactive oxygen species (ROS), neuroinflammatory responses, and apoptosis, resulted in cell death and brain tissue damage. Neurotherapeutics agents are given to affect the pathophysiological pathways and prevent expanding infarct area. Objective: This study aims to analyze the modulation of Gluthatione S-Transferase (GST) and Tyrosine kinase receptor C (TrkC) by 7,8-DHF as neuroprotective agent in ischemic in silico. Methods: This study used in silico simulation to predict 7,8-dihydroxyflavone (DHF) as neuroprotective agent by using PubChem, RCSB, Biovia Discovery Studio, PyRx, and PyMol. This study analyzes the pharmacodynamics, pharmacokinetics, and molecular interactions between 7,8-DHF as a ligand with GST (13GS) and TrkC (6KZC) as protein target, compared to their native ligand. Results: 7,8-DHF may increase intracellular endogenous antioxidants mainly GST and stimulate TrkC to activate further neuron survival signaling. 7,8 DHF has a much lower bond energy (-8.1 Kcal/mol) when it binds to GST compared to the native ligand (-5.9 Kcal/mol). Besides, binding affinity between 7,8-DHF-TrkC was -9 Kcal/mol, while native ligand-TrkC was -10.6 Kcal/mol. This study showed that there were the same amino acid residues between 7,8-DHF-GST and 7,8-DHF-TrkC, compared to their native ligand. Conclusion: As an adaptive response to hypoxia caused by ischemic stroke, these findings are likely to induce protective mechanism through indirectly TrkC activation which regulates neurogenesis and increasing intracellular endogenous antioxidants.